2019
DOI: 10.1155/2019/5731639
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Study of NR2C2, BTG2, TBX19, and CDK2 Expression in 31 Paired Primary/Recurrent Nonfunctioning Pituitary Adenomas

Abstract: This study investigated potential markers for predicting nonfunctioning pituitary adenoma (NFPA) invasion and recurrence by high-throughput tissue microarray analyses. We retrospectively studied two groups of patients: 60 nonrecurrent NFPA cases that included noninvasion and invasion subtypes and 43 recurrent cases that included primary NFPA. A total of 31 paired patient samples were evaluated (12 patients with one surgery and 31 who had undergone two operations, with both tumors analyzed). Expressions of nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…This protein functions as protector of cells from oxidative stress. Overexpression of NR2C2 has been associated with adenoma progression previously (Yao et al 2019). NR2C2 has been downregulated in this study.…”
Section: Discussionsupporting
confidence: 55%
“…This protein functions as protector of cells from oxidative stress. Overexpression of NR2C2 has been associated with adenoma progression previously (Yao et al 2019). NR2C2 has been downregulated in this study.…”
Section: Discussionsupporting
confidence: 55%
“…The role of age in recurrence is controversial. Yao et al and Batista et al both revealed that age was not associated with recurrence (22,23). However, Losa et al indicated that younger age was associated with the possibility of tumor recurrence (24).…”
Section: A B Cmentioning
confidence: 99%
“…For the downregulated intergenic lncRNA, ENST00000432511, the results of high-throughput sequencing revealed BTG2 (PC3|TIS21) as its coexpressed gene. BTG2 encodes antiproliferative factor 2, which is a transcriptional synergistic regulatory factor involved in the regulation of cell differentiation, growth, and survival [23].…”
Section: Data Comparison Between the Lada And Nondiseasedmentioning
confidence: 99%